(3CSFdI Yf (B" (3GSJWYeG CgdgG (B" (3hCLhHI dHYV GdYdeGA YfgGs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe UdGM GdOjf Ndjd GdUaOi cJHJ Edi ehdGfG bGVi GdbVGg GdYdGeI Jbi GdOjf CHj GdMSf Ydi GdSHci GdTGaYi GdeUQi s
(3BNQgG (B:s
(3hEeG EPG JhSWJ HYO Hjf GdbHdjf Ch JCNQJ aEfgG JWdb ai TYHGf hEf JhSWJ bHd Hjf GdHYOjf aai ThGd hGfg JCNQJ aai TYHGf hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs